Evaluation of the quality of water from boreholes selected from the Ejisu-Juaben and Bosomtwi-Atwima-Kwanwoma Districts of the Ashanti region of Ghana - Nkansah, Marian Asantewah (2011)
A Thesis submitted to the Department of Chemistry, Kwame Nkrumah university of Science and Technology in partial fulfillment of the requirements for the degree of Master of Science (Environmental Chemistry), 2005